Involvement of Nitrate Reductase and Pyoverdine in Competitiveness of Pseudomonas fluorescens Strain C7R12 in Soil - Mirleau, Pascal (American Society for Microbiology, 2001)
Involvement of nitrate reductase and pyoverdine in the competitiveness of the biocontrol strain Pseudomonas fluorescens C7R12 was determined, under gnotobiotic conditions, in two soil compartments (bulk and rhizosphere soil), with the soil being kept at two different values of matric potential (−1 and −10 kPa). Three mutants affected in the synthesis of either the nitrate reductase (Nar(−)), the pyoverdine (Pvd(−)), or both (Nar(−) Pvd(−)) were used. The Nar(−) and Nar(−) Pvd(−) mutants were obtained by site-directed mutagenesis of the wild-type strain and of the Pvd(−) mutant, respectively. The selective advantage given by nitrate reductase and pyoverdine to the wild-type strain was assessed by measuring the dynamic of each mutant-to-total-inoculant (wild-type strain plus mutant) ratio. All three mutants showed a lower competitiveness than the wild-type strain, indicating that both nitrate reductase and pyoverdine are involved in the fitness of P. fluorescens C7R12. The double mutant presented the lowest competitiveness. Overall, the competitive advantages given to C7R12 by nitrate reductase and pyoverdine were similar. However, the selective advantage given by nitrate reductase was more strongly expressed under conditions of lower aeration (−1 kPa). In contrast, the selective advantage given by nitrate reductase and pyoverdine did not differ in bulk and rhizosphere soil, indicating that these bacterial traits are not specifically involved in the rhizosphere competence but rather in the saprophytic ability of C7R12 in soil environments.